Role of Ultrasound in the Evaluation of Urinary Bladder Neoplasm with Histopathological Correlation - Islam, AHM Tohurul; Mostafa, Syeda Nazlee; Rahman, Mizanur; Nahar, Ziban (TAJ: Journal of Teachers Association, 2009)
A descriptive study was carried out on 41 consecutive patients of clinically suspected bladder tumor presented with haematuria, which were studied by ultrasonography and was confirmed histopathologically. Per abdominal sonographic scan of KUB region, especially lower abdomen was done in full bladder state in supine position. Bladder lumens as well as peri-vesical structures were also studied. The sensitivity and specificity of ultrasonography were 96.87% and 60% respectively. The accuracy of ultrasonography was 91.89%. Positive predictive value 93.39% and negative predictive value was 75%. Histopathological types of bladder tumor where 90.63% were transitional cell carcinoma, 6.25% were adenocarcinoma and 3.13% were squamous cell carcinoma. The highest incidence was noted in the posterior wall of the bladder (53.13%) followed by lateral walls (35.50%), roof (03.13%) & the bladder neck (06.25%). The peak age incidence was in 5th to 7th decade, having mean age 57.4 ±2.3 years. Male to female ratio was 9.67:1 and most of them having the habit of smoking (81.25%). Highest incidence of bladder tumor was found in subjects belonging to blood group ‘O' (53.13%), followed by ‘A' (25%), ‘B' (18.75%) ‘AB' (3.13%). All the cases belong to Rhesus positive group. Bladder tumor was higher among the low socio-economic group (43.75%), followed by below average (34.38%), average (15.63%) and good (6.25%). Ultrasound is a very useful modality in diagnosis of urinary bladder neoplasm, which is cheap, easily available, noninvasive and negligible discomfort. So, sonographic scan can be recommended as a useful diagnostic modality in respect of urinary bladder neoplasm. doi: 10.3329/taj.v21i2.3797 TAJ 2008; 21(2): 155-159